ANALISIS KEBIJAKAN PENATAUSAHAAN HASIL HUTAN KAYU DALAM IMPLEMENTASI SISTEM VERIFIKASI LEGALITAS KAYU DI KABUPATEN JEPARA - , NOVI TRIYANTO, Wahyu Tri Widayanti, S.Hut., M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Rampant illegal logging in Indonesia encouraged government to implement a Timber Legality Verification System. The purpose of this study was to examine the implementation of the policies that have been implemented in the district of Jepara. This was a qualitative research. The basic method used in this study was a survey method for assessing the effectiveness of policies and the compliance of policy targets. The effectiveness of the policy was assessed using the theory of Edward III, while the analysis document compliance of forest product timber traceability through the wood raw material supply chains. The analysis used in this study was a descriptive analysis. The study was conducted in the district of Jepara by selecting several processing industries in the period December 2013 to January 2014. Data collection was done through observation and interviews. Respondents were selected according to their knowledge and representation between industry players and the government institutions. There is a big number of wood processing industry in Jepara. The chain of custody of timber that has been applied has not followed consistently to the existing regulation. The problem of obtaining in the legal certificate is occurs. Compliance documents proving the legality of timber has been largely ignored by the industry. The problem becomes one of the factors that policy implementation. In addition, the availability of technical officers for the legality of timber document is lacking when compared to the number of industries in Jepara. The result showed the value of the effectiveness of policy and level of adherence to the document of administering forest product based on selected sample district Jepara classified as low. Keywords : Policy Analysis, Timber Tracking, Timber Legality Verification System